body mass and pregnancy in relation to parasite treatment - Carlsson, Anja M.; Albon, Steve D.; Coulson, Stephen J.; Ropstad, Erik; Stien, Audun; Wilson, Ken; Loe, Leif Egil; Veiberg, Vebjørn; Irvine, R. Justin (Dryad Digital Repository, 2018)
one row per observation. Each row is a captured individual. an individual may appear more then once. Columns provide data on date of capture, treatment, body mass, pregnancy status. Description of the variables is in the READ ME file